Measurement of IgG antibodies to Chlamydia trachomatis by commercial enzyme immunoassays and immunofluorescence in sera from pregnant women and patients with infertility, pelvic inflammatory disease, ectopic pregnancy, and laboratory diagnosed Chlamydia psittaci/Chlamydia pneumoniae infection. Issue 3 (1st March 2003) - Jones, C S; Maple, P A C; Andrews, N J; Paul, I D; Caul, E O
Abstract : Background: Screening for Chlamydia trachomatis specific antibodies is valuable in diagnosing asymptomatic pelvic inflammatory disease (PID) and tubal damage following repeated episodes of PID. The assays in current use are unsuitable for screening large numbers of samples so there is a need to develop more suitable assays. Aims: To compare the performance of several commercial C trachomatis enzyme immunoassays (EIAs) (SeroCT, C tracho pep, Medac p-EIA, Vircell and Labsystems C trachomatis IgG EIAs) using major outer membrane protein (MOMP), an inactivated organism EIA (Genzyme Virotech EIA), and a genus specific EIA (Platelia Chlamydia IgG) with the whole cell inclusion immunofluorescence (WIF) assay. In addition, to adapt, using time resolved fluorescence technology, the assay showing the highest correlation with WIF. Methods: Ninety sera from patients presenting with ectopic pregnancies, 187 sera from those with a variety of types of infertility, 33 sera from cases of PID where a fourfold rise in WIF titre occurred, and 90 sera from antenatal clinic attenders were tested. A panel of 36 sera from laboratory diagnosed cases of Chlamydia psittaci / Chlamydia pneumoniae infection was also tested. Results: The Genzyme Virotech EIA showed the highest rank correlation coefficient (0.82) with WIF, particularly at high WIF titres. The MOMP specific assays varied in their correlation with WIF, with rank correlation coefficients ranging from 0.70 (Medac p-EIA) to 0.80 (Vircell EIA). The Genzyme Virotech assay showed poor specificity (5.6%; 95% confidence interval (CI), 0.68% to 18.7%)—it was reactive with 34 of the panel of 36 C psittaci / C pneumoniae positive sera. The MOMP based EIAs showed high specificity, particularly the Medac p-ELISA (97.2%; 95% CI, 85.5% to 99.9%)—only one serum was reactive. In view of the good correlation between WIF and the Genzyme Virotech EIA, a time resolved fluorescence immunoassay (TRFIA) was developed using the Genzyme Virotech antigen. Using an appropriate cut off the TRFIA assay showed excellent correlation with WIF. Conclusions: The TRFIA assay may be useful as a screening assay, possibly in conjunction with one of the highly specific EIAs studied (for example, Medac p-EIA) to confirm the antibody specificity of sera selected by the screening assay.